English and American Studies in German : A Supplement to Anglia. Summaries of Theses and Monographs (De Gruyter, 1969)
The summaries published in English and American Studies in German record university publications (PhD theses as well as post-doctoral theses), independent book publications, and collections dedicated to specific subject areas (festschrifts, yearbooks, conference proceedings).